CORRELATION BETWEEN DERMATOGLIFIA AND ANAEROBIC CAPACITY IN DOWNHILL ATHLETES (Fiep Bulletin - online, 2019)
Abstract: This work aims to associate dermatoglyphics with the power and anaerobic capacity of mountain bikeathletes (downhill), submitted to the Wingate test. Thus, characterizing athletes through dermatoglyphics, evaluating power andanaerobic capacity with Wingate test, then doing data correlation. The population / sample to be surveyed participates in theCatarinense downhill championship, with stages of competition in several cities of Santa Catarina, being the show pilots fromJoinville, Sao Bento do Sul, Schroeder and Jaragua do Sul. There were 19 individuals competing in the downhill Catarinensecircuit, aged between 18 and 35 years, male. The data were collected, in an appropriate environment for this activity, in thedependencies of the University of the Region of Joinville - UNIVILLE, Campus Joinville. It was detected that athletes fromCatarinense had a predominance of class V (44%), that is, they have predominantly aerobic valences, with resistance of speed,agility, coordination and resistance, with low strength index. Class II and III athletes have greater power and anaerobic capacityand fatigue index. The classes II and III, have maximum valence in speed and strength. The relation between the digital drawingsand the anaerobic power, anaerobic capacity and fatigue index was very weak, with no correlation.